SUBCUTANEOUS LEIOMYOSARCOMA OF SUPRA-PUBIC REGION MANAGED WITH WIDE LOCAL EXCISION AND TOTAL PENECTOMY - Nazim, Syed Muhammad; Nusrat, Ayesha; Bashir, Ahmad (Journal of Ayub Medical College Abbottabad, 2023)
Subcutaneous leiomyosarcomas (LMS) are rare soft tissue sarcomas arising from small-to-medium-sized blood vessels. Involvement of the anterior abdominal wall is extremely rare. We present a case of a 72-year-old gentleman who presented with 3 months history of a progressively increasing mass in the supra-pubic region reaching the root of penis without any regional lymphadenopathy. Magnetic resonance imaging (MRI) pelvis showed a large heterogeneous mass in lower abdomen indenting the penile corpora. Complete pathological clearance was achieved by wide excision of the mass with total penectomy and cutaneous urethrostomy. The patient received adjuvant radiation therapy and is free of local recurrence or distant metastasis two years after the surgery.